2016
DOI: 10.1186/s11671-016-1474-x
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Lignosulfonate-Assisted Synthesis of Hierarchical Nanoflake-Array-Flower ZnO Nanomaterials in Mixed Solvents and Their Photocatalytic Performance

Abstract: With the assistance of sodium lignosulfonate, hierarchical nanoflake-array-flower nanostructure of ZnO has been fabricated by a facile precipitation method in mixed solvents. The sodium lignosulfonate amount used in our synthetic route is able to fine-tune ZnO morphology and an abundance of pores have been observed in the nanoflake-array-flower ZnO, which result in specific surface area reaching as high as 82.9 m2 · g−1. The synthesized ZnO exhibits superior photocatalytic activity even under low-power UV illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A mechanism (Figure ) was proposed for the formation of the yolk–shell structured carbon spheres with pollen-like surface based on the above characterization results and the general aspects of the soft templating and hydrothermal carbonization. The formation of surfactant micelles relies on the fact that surfactant molecules energetically prefer a parallel molecular arrangement, which would result in the formation of bilayer micelles. , When the micelles aggregated extensively, their total energy was reduced by bending and further self-assembling. , Furthermore, due to the highly branched structure and steric hindrance effect of lignosulfonate, lignosulfonate preferentially assembled at the outer position of the double layers of micelles, while linear structure P123 was located at the inner position. On the other hand, it has been reported that the soft templates do provide appropriate nucleation and growth sites for the assembled particles and modulate the formation process at the same time .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mechanism (Figure ) was proposed for the formation of the yolk–shell structured carbon spheres with pollen-like surface based on the above characterization results and the general aspects of the soft templating and hydrothermal carbonization. The formation of surfactant micelles relies on the fact that surfactant molecules energetically prefer a parallel molecular arrangement, which would result in the formation of bilayer micelles. , When the micelles aggregated extensively, their total energy was reduced by bending and further self-assembling. , Furthermore, due to the highly branched structure and steric hindrance effect of lignosulfonate, lignosulfonate preferentially assembled at the outer position of the double layers of micelles, while linear structure P123 was located at the inner position. On the other hand, it has been reported that the soft templates do provide appropriate nucleation and growth sites for the assembled particles and modulate the formation process at the same time .…”
Section: Resultsmentioning
confidence: 99%
“…The formation of surfactant micelles relies on the fact that surfactant molecules energetically prefer a parallel molecular arrangement, which would result in the formation of bilayer micelles. 44,45 When the micelles aggregated extensively, their total energy was reduced by bending and further selfassembling. 44,46 Furthermore, due to the highly branched structure and steric hindrance effect of lignosulfonate, lignosulfonate preferentially assembled at the outer position of the double layers of micelles, while linear structure P123 was located at the inner position.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…24 In addition, spheroidal and irregular disklike shapes of the LS nanocomposite have been observed in some studies. 25,26 Related research has speculated that the structures of LS complexes could be controlled by electrostatic repulsion. 22 In our previous research, we found that the LS nanocomposite with a variety of morphologies, including nanospheres, nanocubes, nanorods, nano-octahedrons, and nanobranches, can be synthesized in different anion solutions and under different environmental pH values.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lignin is the second most abundant botanical polymer and the unique scalable renewable feedstock consisting of aromatic monomers. It presents excellent UV-absorbing and antioxidant properties due to its aromatic skeleton and phenolic hydroxyl groups. Ugartondo et al and Tortora et al demonstrated that industrial lignins and their derivatives are safe to human cells and exhibit good biocompatibility. Therefore, lignin-based products have been investigated as UV-blocker, antioxidant, macromolecular surfactant, , nutraceutical, and drug delivery . With the development of biorefinery, more and more byproduct enzymatic hydrolysis lignin (EHL) is produced, which maintains most of the original structure of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…21−23 Ugartondo et al 24 and Tortora et al 25 demonstrated that industrial lignins and their derivatives are safe to human cells and exhibit good biocompatibility. Therefore, lignin-based products have been investigated as UV-blocker, 21 antioxidant, 26 macromolecular surfactant, 27,28 nutraceutical, and drug delivery. 29 With the development of biorefinery, more and more byproduct enzymatic hydrolysis lignin (EHL) is produced, which maintains most of the original structure of lignin.…”
Section: ■ Introductionmentioning
confidence: 99%